Phage Biocontrol Applications in Food Production and Processing - Vikram, Amit; Woolston, Joelle; Sulakvelidze, Alexander (Current Issues in Molecular Biology, 2021)
Bacteriophages, or phages, are one of the most, if not the most, ubiquitous organisms on Earth. Interest in various practical applications of bacteriophages has been gaining momentum recently, with perhaps the most attention (and most regulatory approvals) focused on their use to improve food safety. This approach, termed 'phage biocontrol' or 'bacteriophage biocontrol', includes both pre- and post-harvest application of phages as well as decontamination of the food contact surfaces in food processing facilities. This review focuses on post-harvest applications of phage biocontrol, currently the most commonly used type of phage mediation. We also briefly describe various commercially available phage preparations and discuss the challenges still facing this novel yet promising approach.